Educação básica e inteligência artificial: perspectivas, contribuições e desafios - Gatti, Francielle Nogueira (2019)
This research is part of the New Technologies in Education research line of the Postgraduate Program in Education: curriculum of Pontifícia Universidade Católica de São Paulo. It aims to verify the incidence and subjects treated by the Brazilian researchers in the interface education and artificial intelligence. It has a qualitative approach through literature review. It was carried out a survey of theses and dissertations adherent to the interface between education and artificial intelligence, in basic education, published in Brazil from 1995 to 2018. After the cuts the study counted on the qualitative reading of seventeen publications between dissertations and theses that were analyzed in agreement with pre-established criteria, the texts were observed as to their main interlocutors, pedagogical currents, to which they were destined, among other categories created for the analysis. The main considerations about the research findings: AI is a recurring theme among publications; the research that served as the basis for this study revealed the strong characteristic of using AI as a tool and not as an object of study in basic education; most of the research produced on the subject comes from Post-Graduation Programs in the area of Computer Science or Engineering, few researches in Education Programs; in no research the AI figures as content to be studied in school and only one study discusses the curricular application